Modulation of adipose tissue metabolism by microbial-derived metabolites - Liu, Wenyun; Yang, Ge; Liu, Pinyi; Jiang, Xin; Xin, Ying (Frontiers in Microbiology, 2022)
Obesity and its complications, including type 2 diabetes, cardiovascular disease, and certain cancers, have posed a significant burden on health and health care systems over the years due to their high prevalence and incidence. Gut microbial derivatives are necessary for the regulation of energy metabolism and host immunity, as well as for maintaining homeostasis of the intestinal environment. Gut flora metabolites may be a link between gut microbes and diseases, such as obesity, and help understand why alterations in the microbiota can influence the pathophysiology of human disease. This is supported by emerging evidence that microbial-derived metabolites, such as short-chain fatty acids (SCFA), bile acids, tryptophan (Trp), trimethylamine-N-oxide (TMAO), and lipopolysaccharides (LPS), can be beneficial or detrimental to the host by affecting organs outside the gut, including adipose tissue. Adipose tissue is the largest lipid storage organ in the body and an essential endocrine organ that plays an indispensable role in the regulation of lipid storage, metabolism, and energy balance. Adipose tissue metabolism includes adipocyte metabolism (lipogenesis and lipolysis), thermogenesis, and adipose tissue metabolic maladaptation. Adipose tissue dysfunction causes the development of metabolic diseases, such as obesity. Here, we review the current understanding of how these microbial metabolites are produced and discuss both established mechanisms and the most recent effects of microbial products on host adipose tissue metabolism. We aimed to identify novel therapeutic targets or strategies for the prevention and treatment of obesity and its complications.